“Not a Note in My Head”: Reflecting on Musical Identity through Kodály-inspired Community Music Therapy - Coughlan, Edel (Voices: A World Forum for Music Therapy, 2024)
Research on the health and well-being benefits of participating in music therapy initiatives such as group singing and drumming is steadily increasing. Community music therapy aims to render such initiatives more accessible to people who are marginalised due to race, gender, age and socio-economic status for example. This study focuses on people who are reluctant to participate in such musical initiatives because of negative self-beliefs about their musical identity. Previous studies have investigated the reasons behind these negative self-beliefs among certain populations, but there is a lack of research surrounding music therapy interventions that address this issue. This study aimed to explore reasons behind people’s negative self-beliefs about their musical identity among an Irish population. This study further aimed to investigate whether an intervention involving a Kodály-inspired community music therapy approach could produce a shift in those negative self-beliefs. Data gathered from seven participants during semi-structured preliminary and exit interviews and a 3-week focus group intervention was analysed using thematic analysis. It was found that negative self-beliefs about one’s musical identity were constructed from negative early experiences of music education and through adopting Irish society’s tendency to polarise people into musical and non-musical categories. These factors have contributed to many Irish people’s reluctance to participate in active music-making opportunities. Findings also revealed that participating in a Kodály-inspired community music therapy intervention produced a positive shift in people’s musical identity and a potential to consider participating in future active music-making opportunities. A Kodály-inspired community music therapy model of practice is proposed.